Headache in radiologically isolated syndrome: a hint toward imminent conversion: a case report - Masoud Etemadifar; Hasan Kaveyee; Parto Zohrabi; Amir Mohammad Jozaie; Mehri Salari; Yasin ebne-ali-heydari (Journal of Medical Case Reports, 2025)
Abstract Background Headaches are more prevalent in patients with multiple sclerosis compared with the general population. However, headaches are still considered a rare symptom of multiple sclerosis, especially when they appear as an initial symptom. The occurrence of a headache as a symptom of radiologically isolated syndrome (RIS) is uncommon, and it can significantly increase the likelihood of developing multiple sclerosis. Case presentation We report the case of a 36-year-old Iranian woman experiencing severe unilateral headaches without other multiple sclerosis symptoms. Despite normal physical and laboratory exams, cerebrospinal fluid analysis showed positive oligoclonal bands. Magnetic resonance imaging (MRI) revealed multiple demyelinating plaques consistent with RIS. She was treated with dimethyl fumarate. Subsequent MRI confirmed multiple sclerosis by showing new gadolinium-enhanced lesions. After 3 months of dimethyl fumarate treatment, her headache intensity decreased, and she remained otherwise symptom free. Written informed consent was obtained from the patient. Conclusion Effectively managing headaches in patients with RIS is a challenge for clinicians to improve their quality of life and delay the progression of multiple sclerosis.